Analysis Of The Influence Of Service Quality, Brand Image And Branch Office Location On Banking Customer Decisions In Money Saving In Indonesia - Luh Komang Candra Dewi; Bahtiar Efendi; Errie Margery; Arnold Sultantio Hutabarat; Prety Diawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to examine how customers’ decisions to save at religious banks are influenced by factors such as location, service quality, and brand image. Purposive sampling is the technique employed for sampling. There were one hundred respondents in this survey who hold savings accounts with Islamic banks. Multiple liner regression is the analysis technique employed in this study. The findings demonstrated that the customer’s decision to save at an religious bank was significantly influenced, both partially and simultaneously, by the factors of brand image, service quality, and location.